PENGARUH PENGALAMAN, INDEPENDENSI, SKEPTISME PROFESIONAL, KOMPETENSI, DAN KOMUNIKASI INTERPERSONAL AUDITOR KAP TERHADAP PENDETEKSIAN KECURANGAN (Studi Empiris Pada KAP Di Wilayah Pekanbaru, Medan, dan Batam) - Febrina Ramadhany; Zirman -; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research aims to examine the impact of experience, independence, professional skepticism, competence, and auditor interpersonal communication detection for fraud. Object of this research is Public Accountant Firm in Pekanbaru, Medan, and Batam. The sample of this research was collected by using convenience sampling. There are one hundred and twenty five questionnaires which were spread out but only ninety nine or seventy nine point two percent questionnaires returned. That data are analyzed by multiple linear regression method and using SPSS for windows version 20. The result of this research show that experience, independence, professional skepticism, competence, and auditor interpersonal communication significantly affect the detection of fraud. The result of this research also show that experience, independence, professional skepticism, competence, and auditor interpersonal communication simultaneously affect the detection of fraud. The research also shows that the auditor’s professional skepticism variable is the most dominant variable affect detection for fraud.Keywords: experience, independence, professional skepticism, competence, interpersonal communication, and fraud detection.